1995
DOI: 10.1016/0304-3959(95)00084-6
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fentanyl and sufentanil infusion substitution for morphine intolerance in cancer pain management

Abstract: Eleven patients with cancer pain in a palliative care and chronic pain service required cessation of morphine due to unacceptable opioid side effects. In this retrospective study fentanyl was evaluated as a second-line subcutaneously infused opioid. Starting doses ranged from 100 to 1000 micrograms/24 h, and the duration of fentanyl infusion was 3-70 days. The clinically derived mean relative potency of fentanyl to morphine infusions was 68:1 (SD +/- 23; range: 15-100), and we now recommend cautious dose conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 7 publications
4
60
0
Order By: Relevance
“…Long-term morphine injections to rats induced tolerance to the analgesic responses of both morphine and fentanyl, but long-term administration of an equieffective dose of fentanyl did not produce tolerance (Paronis and Holtzman, 1992). Similarly, patients with cancer-related pain refractory to morphine do not exhibit tolerance to fentanyl or sufentanil (Paix et al, 1995). These data suggest that although morphine and fentanyl interact with MOR, they may induce distinct biochemical cellular adaptations.…”
Section: Discussionmentioning
confidence: 85%
“…Long-term morphine injections to rats induced tolerance to the analgesic responses of both morphine and fentanyl, but long-term administration of an equieffective dose of fentanyl did not produce tolerance (Paronis and Holtzman, 1992). Similarly, patients with cancer-related pain refractory to morphine do not exhibit tolerance to fentanyl or sufentanil (Paix et al, 1995). These data suggest that although morphine and fentanyl interact with MOR, they may induce distinct biochemical cellular adaptations.…”
Section: Discussionmentioning
confidence: 85%
“…Fentanyl causes less histamine release, a lower incidence of constipation and affords greater cardiovascular stability than morphine. 60 Fentanyl is rapidly metabolized and eliminated almost exclusively by the liver with only 5%-10% excreted unchanged in the urine. 61 Its metabolites are considered to be inactive.…”
Section: Fentanylmentioning
confidence: 99%
“…OIN presents with excessive sedation, delirium, hallucinations, myoclonus, and seizures, which are consequences of the accumulation of both the parent opioid and its metabolites [4]. Opioid rotation (OR), which is substituting one opioid by another, is recommended for intolerable side effects like OIN and for inadequate pain control despite dose escalation [5][6][7][8][9][10][11][12]. A recent study from our group showed that OR was conducted in 31% of cancer outpatients receiving strong opioids, with a 65% success rate.…”
Section: Introductionmentioning
confidence: 99%